School s’ Violence and its relation to academic Failed and School s’ Drop - Out among Intermediate stage Pupils (Journal Of Educational and Psychological Researches, 2011)
The present research aims to know the relation of Violence on academic Failed and School s’ Drop - out among Intermediate stage Pupils. The sample of the research reached (400) male and female pupils (failed and not failed ), and (69) male and female that Drop – out from Intermediate stage. The researcher used scale of Violence that constructed by (AL- qaysi , 2004) after she got Validity and Reliability to it . So that she used t- test for one sample, t- test for two independent sample, and Person correlation coefficient as a statistical means. The research reached to the results that indicates raising of level of Violence among the Intermediate stage pupils (failed and not failed) and the male and female that Drop – out from Intermediate stage. So the Violence affected on academic Failed and School s’ Drop - out among Intermediate stage Pupils. Finally and according to the results of the research  the researcher put some Recommendations and Suggestions.